Territories in dispute: habitat self-management as a strategy for the reappropriation of urban commons? - Cecilia Zapata, María (Revista de Estudios Andaluces, 2024)
The hypercommodification process imposed by the capitalist restructuring of the 1970s found in the cities the preferred possibilities for the accumulation of real estate and, therefore, the dispossession of broad social sectors. In Buenos Aires (Argentina), this scenario created gaps for the emergence of self-managed production of habitat experiences with the capacity to reappropriate urban commons, that implied a concrete dispute in productive, communitarian and cultural matters. From a qualitative methodology based on grounded theory and from the identification of specific dimensions of analysis, this article reflects on the material and symbolic disputes existing around the self-management practices in the inhabited experiences of the Housing Self-Management Program. It is shown that only some projects were involved in concrete practices of habitat self-management, disputing the reappropriation of urban commons. This was to the detriment of a set of experiences that were recaptured by the mercantile logic of neoliberal urbanism.